2022
DOI: 10.3390/math10050770
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making of Transnational Supply Chain Considering Tariff and Third-Party Logistics Service

Abstract: Countries’ economic policies, such as tariff barriers, have a profound impact on the global economy and international trade. The imposition of tariffs seriously disturbs the global trade and supply chain operations. This paper studies a supply chain composed of an overseas manufacturer, a domestic supplier and a third-party integrated international logistics service provider. A three-level decentralized leader-follower decision-making model and its variant--leader-follower alliance decision-making models are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For example, Zhang et al(2019)introduced government subsidy policies and carbon emission trading policies to guide cold chain logistics enterprises to carry out energy saving and emission reduction transformation of cold storage, and applied this method to the decision-making of regional cold chain logistics system in Wuhan, Hubei Province [27]. Hu et al (2022) established a logistics cooperation model of cross-border two-way supply chain under the benefit sharing and cost sharing policy, and put forward strategies for effective cooperation and coordination of supply chain and reducing the impact of tariffs on the global trading system [28]. Babagolzadeh et al (2022) analyzed the structure and decision of regional distribution network under different government subsidy schemes, and the results showed that the introduction of subsidies can effectively reduce the total logistics cost [29].…”
Section: Research On the Construction Of Logistics Channels With Gove...mentioning
confidence: 99%
“…For example, Zhang et al(2019)introduced government subsidy policies and carbon emission trading policies to guide cold chain logistics enterprises to carry out energy saving and emission reduction transformation of cold storage, and applied this method to the decision-making of regional cold chain logistics system in Wuhan, Hubei Province [27]. Hu et al (2022) established a logistics cooperation model of cross-border two-way supply chain under the benefit sharing and cost sharing policy, and put forward strategies for effective cooperation and coordination of supply chain and reducing the impact of tariffs on the global trading system [28]. Babagolzadeh et al (2022) analyzed the structure and decision of regional distribution network under different government subsidy schemes, and the results showed that the introduction of subsidies can effectively reduce the total logistics cost [29].…”
Section: Research On the Construction Of Logistics Channels With Gove...mentioning
confidence: 99%
“…In order to investigate the effects of cross-border variables like tariff deficiencies and transportation costs on cross-border supply networks, Villegas and Ouenniche [ 32 ] built a model of production and distribution planning for cross-border supply chains. International manufacturers, domestic suppliers, and third-party integrated international logistics service providers make up the supply chain decision-making model that Hu et al [ 33 ] built. The study demonstrates how the imposition of tariffs has seriously disrupted the functioning of global trade and supply chains.…”
Section: Introductionmentioning
confidence: 99%